2011
DOI: 10.4187/respcare.00801
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Randomized Controlled Trial to Assess Effectiveness of Nasal High-Flow Oxygen in Intensive Care Patients

Abstract: OBJECTIVE:In a cardiothoracic and vascular intensive care unit, to compare nasal high-flow (NHF) oxygen therapy and standard high-flow face mask (HFFM) oxygen therapy in patients with mild to moderate hypoxemic respiratory failure. METHODS: In a prospective randomized comparative study, 60 patients with mild to moderate hypoxemic respiratory failure were randomized to receive NHF or HFFM. We analyzed the success of allocated therapy, noninvasive ventilation rate, and oxygenation. RESULTS: Significantly more NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
174
4
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(190 citation statements)
references
References 21 publications
6
174
4
6
Order By: Relevance
“…The study showed that compared to standard oxygen therapy, HFNC did not improve atelectasis, oxygenation, respiratory rate, or dyspnea, nor did it reduce rates of failure of allocated therapy. Although these results are in accordance with previous ones [15], they are in contradiction with the recent study by Maggiore et al that showed that HFNC improved oxygenation, comfort, and reintubation rate in the post-extubation setting [7]. However, this study was conducted in patients with acute respiratory failure from pneumonia and trauma, which are quite different from obese patients extubated right after cardiac surgery.…”
contrasting
confidence: 83%
“…The study showed that compared to standard oxygen therapy, HFNC did not improve atelectasis, oxygenation, respiratory rate, or dyspnea, nor did it reduce rates of failure of allocated therapy. Although these results are in accordance with previous ones [15], they are in contradiction with the recent study by Maggiore et al that showed that HFNC improved oxygenation, comfort, and reintubation rate in the post-extubation setting [7]. However, this study was conducted in patients with acute respiratory failure from pneumonia and trauma, which are quite different from obese patients extubated right after cardiac surgery.…”
contrasting
confidence: 83%
“…These encouraging results were further confirmed by the same group of authors 1 year later in a prospective observational study on patients with ARF caused by community-acquired pneumonia and sepsis [24]. Moreover, NHF may be more effective in treating mild to moderate hypoxaemic ARF compared to oxygen delivered through a face mask, with fewer desaturations and less need for NIV, as reported in a prospective randomised study by PARKE et al [25].…”
Section: Discussionmentioning
confidence: 57%
“…Patients on NHF had significantly fewer desaturations and succeeded more in their allocated therapy, with less need for NIV or intubation, although respiratory (SpO 2 , respiratory rate and forced expiratory volume in 1 s) and cardiovascular (systolic and diastolic arterial pressure and heart rate) variables did not differ between groups. Positive airway pressure, enabling the recruitment of atelectatic lung areas, along with facilitation of mucociliary clearance by the heated and humidified gas administered by NHF, were the possible key features that improved overall treatment effectiveness in both studies [25,45], given that atelectasis is the more common respiratory complication after surgery, presenting in 90% of patients undergoing general anaesthesia [42]. The specific mechanisms of benefits of NHF on post-surgical respiratory complications were studied further by CORLEY et al [5] and it was found that NHF compared to low-flow oxygen on post-cardiac surgery patients significantly increased mean airway pressure by 3.0 cmH 2 O, tidal volume by 10.5% and EELV by 25.6%, regardless of whether they breathed with the mouth open or closed.…”
Section: No Benefitmentioning
confidence: 99%
See 2 more Smart Citations